Transplantation of Autologous Mesenchymal Stem Cells for End-Stage Liver Cirrhosis: A Meta-Analysis Based on Seven Controlled Trials - Xiang-Rui Ma; Ya-Ling Tang; Ming Xuan; Zheng Chang; Xiao-Yi Wang; Xin-Hua Liang (Gastroenterology Research and Practice)
Background. The bone marrow-derived mesenchymal stem cells (BM-MSCs) have demonstrated great potential as regenerative medicine in different therapeutic applications. This study aims to pool previous controlled clinical trials to make an update assessment of the effectiveness of BM-MSC transplantation on end-stage liver cirrhosis. Methods. Relevant studies published between January 1990 and June 2014 were searched among Pubmed, Embase, and ClinicalTrial.gov. A meta-analysis was performed to assess the effect of BM-MSCs on liver function indicators, including Models of End-Stage Liver Disease (MELD) score, serum albumin (g/L), total bilirubin (mg/dl), Prothrombin concentration (%), and alanine aminotransferase (ALT) (U/L). Results. BM-MSCs therapy could significantly improve liver function in patients with end-stage liver cirrhosis, in terms of MELD score, serum albumin, total bilirubin, and prothrombin concentration, at least during the half year after transplantation. Conclusions. Due to BM-MSCs’ immunomodulatory functions and the potential to differentiate into hepatocytes, they are a promising therapeutic agent to liver cirrhosis. Considering currently available evidence, this therapy is relatively safe and effective in improving liver function. However, how different variables should be controlled to optimize the therapeutic effect is still not clear. Thus, future mechanism studies and clinical trials are required for this optimization.